2015
DOI: 10.5114/pm.2015.54347
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain in women before and after menopause

Abstract: Low back pain is a massive problem in modern population, both in social and economic terms. It affects large numbers of women, especially those aged 45-60. Going through a perimenopausal period is associated with many symptoms, including low back pain.This paper is a review of published research on the association between the perimenopausal age and low back pain. PubMed databases were investigated. After the search was narrowed to “menopausal status, back pain”, 35 studies were found. Seven studies, which suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
0
14
0
5
Order By: Relevance
“…Research has shown how perimenopausal stage of life is associated with an increased incidence of chronic pain. Given that the sample consisted of elder women only it is possible that changes in menopausal status could have contributed to variation in pain (for an overview, see Kozinoga et al., ). Finally, a general problem with the twin design attenuation of associations due to random measurement error in exposure which will be higher in the within‐pair estimate, leading within‐pair associations to be weaker than corresponding unpaired associations, even in the absence of confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown how perimenopausal stage of life is associated with an increased incidence of chronic pain. Given that the sample consisted of elder women only it is possible that changes in menopausal status could have contributed to variation in pain (for an overview, see Kozinoga et al., ). Finally, a general problem with the twin design attenuation of associations due to random measurement error in exposure which will be higher in the within‐pair estimate, leading within‐pair associations to be weaker than corresponding unpaired associations, even in the absence of confounding.…”
Section: Discussionmentioning
confidence: 99%
“…This increasing trend of the rate of LBP is recorded worldwide and might be related to women’s involvement in the workforce, while their house chores do not diminish [ 69 , 70 ]. LBP’s risk factors specific to women comprise exposure to musculoskeletal loads due to pregnancy [ 71 , 72 , 73 ]; menstruation [ 74 , 75 ]; menopausal [ 66 , 76 , 77 ]; hormone [ 66 , 78 ]; osteoporosis [ 68 , 79 ]; low bone mineral density [ 80 , 81 ]; and conditions associated with ageing [ 59 , 82 ]. In contrast, certain studies show that men have a higher rate of LBP [ 1 , 2 ], especially those involved in heavy physical work and repetitive movements [ 1 , 2 , 6 , 38 , 39 ].…”
Section: Causes and Risk Factors Of Lower Back Painmentioning
confidence: 99%
“…This increasing trend of the rate of LBP is recorded worldwide and might be related to women's involvement in the workforce, while their house chores do not diminish [69,70]. LBP's risk factors specific to women comprise exposure to musculoskeletal loads due to pregnancy [71][72][73]; menstruation [74,75]; menopausal [66,76,77]; hormone [66,78]; osteoporosis [68,79]; low bone mineral density [80,81]; and conditions associated with ageing [59,82]. In contrast, certain studies show that men have a higher rate of LBP [1,2], especially those involved in heavy physical work and repetitive movements [1,2,6,38,39].…”
Section: Age and Gendermentioning
confidence: 99%